(untitled) - The World Bank (Washington, DC 20433, 2002)
This atlas provides easy-to-read colorful world maps, tables and graphs highlighting key social, economic and environmental data for 206 countries. The atlas parallels the six thematic sections of the World Development Indicators: world vies, people, environment, economy, states and markets, and global links. The book is designed to be suitable for use in the library, classroom and office.
Keywords: Dân số,Tổng sản phẩm quốc gia,Population,Gross national product; Bản đồ,Thống kê,Bản đồ,Maps,Statistics,Maps